1998
DOI: 10.1001/archinte.158.12.1333
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Without Sleep Apnea Is Associated With Daytime Sleepiness

Abstract: Background: Daytime sleepiness and fatigue is a frequent complaint of obese patients even among those who do not demonstrate sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
171
3
7

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(209 citation statements)
references
References 17 publications
21
171
3
7
Order By: Relevance
“…The limited number and possible selection of participants make it difficult to draw general conclusions. However, the similar results of our large, epidemiological data and of the smaller studies with more precise diagnostic methodology 24,45 make it possible to conclude that even without OSA, obesity is associated with sleep disturbances and daytime tiredness.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The limited number and possible selection of participants make it difficult to draw general conclusions. However, the similar results of our large, epidemiological data and of the smaller studies with more precise diagnostic methodology 24,45 make it possible to conclude that even without OSA, obesity is associated with sleep disturbances and daytime tiredness.…”
Section: Discussionsupporting
confidence: 73%
“…12,16,44 Only a couple of studies have shown a relationship between objectively measured indicators of self-reported sleep quality (for example increased sleep latency, lower proportion of Rapid Eye Movement (REM) sleep and frequent awakenings and increased nocturnal motor activity) and daytime tiredness in individuals with obesity and without OSA. 24,26,45 Compared to our study, the above studies used laboratory-based diagnosis of OSA or nocturnal breathing patterns. The limited number and possible selection of participants make it difficult to draw general conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…After resection of craniopharyngiomas, children will lose their ability to downregulate appetite, demonstrate abnormal food-seeking behavior, and rapidly gain weight. 2,3,6,7,51,52 This can result in daytime somnolence either directly 20 or secondary to OSA. 14,15,19 Our observation that in the 2 morbidly obese patients MSLT scores did not change significantly on documented optimal CPAP treatment suggests that their sleepiness was not caused by sleep-disordered breathing.…”
Section: Figmentioning
confidence: 99%
“…20 When OSA exists, therapy with continuous positive airway pressure (CPAP) is effective and usually results in a substantial improvement of daytime vigilance. [21][22][23] Therefore, a patient who has OSA and is regularly treated with CPAP at an optimal pressure is not expected to be severely sleepy, although some residual sleepiness may remain.…”
mentioning
confidence: 99%
“…In this regard, Vgontzas et al recently reported that obese patients can be sleepier than normal-weight controls during the daytime even if they do not demonstrate any degree of sleep disorder breathing. 16 This study, performed by full-night polysomnography, aimed to investigate the prevalence and severity of sleep breathing disorder and loud snoring in obese patients, and the possible independent in¯uence of body mass index (BMI) and body fat distribution on these alterations. The possibility of a difference in daytime sleepiness between nonapnoeic obese and normal-weight subjects was also examined.…”
Section: Introductionmentioning
confidence: 99%